Leitmann's direct method of optimization for absolute extrema of certain problems of the calculus of variations on time scales - Malinowska, A.B.
The fundamental problem of the calculus of variations on time scales concerns the minimization of a delta-integral over all trajectories satisfying given boundary conditions. This includes the discrete-time, the quantum, and the continuous/classical calculus of variations as particular cases. In this note we follow Leitmann's direct method to give explicit solutions for some concrete optimal control problems on an arbitrary time scale. © 2010 Elsevier Inc. All rights reserved.